Reading for Pleasure and Motivations of Children and Teenagers - Gervais, Hélène, 1981- (2010)
The objective of this study is to discover what motivates children and teenagers to read for pleasure. This research was conducted using qualitative methods by carrying on in-depth interviews with ten young people aged between ten and fifteen years old. Two observations in one of the biggest public libraries in Iceland were also conducted. Data was carefully coded, classified in main themes and analysed. The main results show that children‘ and teenagers‘ readings are varied in content and in form as they enjoy as much fiction as nonfiction and that they read from different printed media as well as electronic material. They mostly read in Icelandic and in English. Parents have a great influence on their children‘s reading habits and they act as reading material providers as well as models. Older siblings also have a great impact on their brothers‘ and sisters‘ readings. Children and teenagers seem to read for four main reasons which are (1) learning, (2) getting attached to characters, (3) be entertained and imagine, and (4) be creatively stimulated. Most participants used their school libraries more than public libraries and there is not much communication between them and library employees.